2013 IEEE 78th Vehicular Technology Conference (VTC Fall) 2013
DOI: 10.1109/vtcfall.2013.6692106
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model of Proportional Fair Scheduling in Interference-Limited OFDMA/LTE Networks

Abstract: Abstract-Various system tasks like interference coordination, handover decisions, admission control etc. in upcoming cellular networks require precise mid-term (spanning over a few seconds) performance models. Due to channel-dependent scheduling at the base station, these performance models are not simple to obtain. Furthermore, upcoming cellular systems will be interferencelimited, hence, the way interference is modeled is crucial for the accuracy. In this paper we present an analytical model for the SINR dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Meanwhile, in [3] the SINR distribution is assumed as Gaussian distributed. Simulations and analytical evaluations from [4] showed that both these simplifications are very similar in rate prediction performance. On the other side, the SINR distribution is not exponential and a precise modelling of the SINR together with the consideration of the dynamic resource allocation has a significant divergence from the approximate model [4].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, in [3] the SINR distribution is assumed as Gaussian distributed. Simulations and analytical evaluations from [4] showed that both these simplifications are very similar in rate prediction performance. On the other side, the SINR distribution is not exponential and a precise modelling of the SINR together with the consideration of the dynamic resource allocation has a significant divergence from the approximate model [4].…”
Section: Introductionmentioning
confidence: 91%
“…Simulations and analytical evaluations from [4] showed that both these simplifications are very similar in rate prediction performance. On the other side, the SINR distribution is not exponential and a precise modelling of the SINR together with the consideration of the dynamic resource allocation has a significant divergence from the approximate model [4]. Nevertheless, the work presented there did not consider multiple interfering sources which are in general present in practical LTE network deployments.…”
Section: Introductionmentioning
confidence: 91%
“…Some users who can't be allocated resources to, are in a completely outage state. It is necessary to suppress the inter-cell interference in the HetNets while guaranteeing the fairness of communication [11], [12]. Then the goal of optimization is no longer maximizing the number of users above the SINR threshold in the network.…”
Section: Fairness Constraintmentioning
confidence: 99%
“…Considering the instantaneous SINR γj,n(t) as a random variable Zj,n, then from [7] the rate expectation Rj,n(p k,n (t)) for PFS based systems can be computed as:…”
Section: Problem Statementmentioning
confidence: 99%
“…So two fundamental problems are to be solved: (i) Modelling the expected system performance and (ii) Optimizing the power allocations accordingly. We have already addressed both these issues: In [7] we have addressed stochastic performance models for interference limited LTE systems. In [8] we have then fundamentally addressed the issue of solving the optimization problem.…”
Section: Introductionmentioning
confidence: 99%